Performance analysis of moth flame optimization algorithm for AGC system. (3rd April 2019) - Mohanty, Banaja
Abstract: In this paper, an attempt has been made for comprehensive study of proportional-integral-double-derivative(PIDD) controller to solve automatic generation control (AGC) problem by applying moth flame optimization algorithm (MFOA). At first two unequal areas of thermal system is considered and the gains of PID/IDD/PIDD controller are optimized using MFOA technique. Simulation study depicted that MFOA-optimized PIDD controller provides better system performances considering settling time, overshoot and undershoot of area frequency and deviations in tie-line power as compared to other optimization techniques considered in this paper. The generation rate constraint (GRC) is included for two-area thermal system and dynamic stability of the system is investigated and compared with recent competitive algorithms. Further, the study is extended to non-linear AGC system with diverse source of generation. Generating unit in each control area consists of hydro, thermal and nuclear generation. Sensitivity analysis reveals that the MFOA-optimized PIDD controller parameter obtained at nominal condition need not necessary to change for wide changes in system parameters and with variation in random step load perturbation.